Metabolic syndrome is inversely related to soluble receptor for advanced glycation end products: a study in mother-infant pairs - Klenovicsova, K.; Boor, P.; Hrachova, J.; Furkova, K.; Sebekova, K. (Вiopolymers and Cell, 2011)
Aim. In the elderly subjects metabolic syndrome (MetS) seems to be associated with low levels of circulating protective soluble receptor for advanced glycation end products (sRAGE). This secondary study aimed to answer whether this phenomenon is manifested from early childhood. Methods. 73 mothers and their 77 infants (4-to-12-months of age) were included in the study. Mothers were classified according to the presence of MetS components as negative (n = 32), those with pre-MetS (insulin resistance + 1 sign of MetS, n = 27) and overt MetS (n = 14). sRAGE and carboxymethyllysine (CML) were determined in the mothers and the infants. Results. Mothers with pre- and overt MetS displayed lower sRAGE levels, while in their children only a trend towards decline was observed. sRAGE levels significantly and inversely correlated with insulin sensitivity and BMI/body weight. No difference in CML levels across the groups was observed. Conclusions. Metabolic syndrome is associated with decreased levels of sRAGE in the mothers and a tendency towards decline of sRAGE in their offspring. Infants of mothers with MetS maintain normoglycemia on the account of higher insulin levels. Keywords: metabolic syndrome, mother-child pairs, QUICKI, sRAGE, insulin resistance, CML.